Identification of risk factors for postoperative complications after right colectomy and low anterior resection in patients ≥85 years old with colorectal cancer using the National Clinical Database - Tomonori Akagi; Shiori Nishimura; Yoshitake Ueda; Masafumi Inomata; Hidefumi Shiroshita; Shuji Takiguchi; Yoshiharu Sakai; Hiraku Kumamaru; Hideki Ueno; Yuko Kitagawa (Annals of Gastroenterological Surgery)
Abstract Aim The purpose of this study was to evaluate factors associated with surgical outcomes and postoperative complications (Grade ≥3 by Clavien–Dindo classification) of right hemicolectomy (RH) and low anterior resection (LAR) for colorectal cancer in patients ≥85 years old. Methods We retrospectively analyzed National Clinical Database (NCD) data on patients aged ≥85 years who underwent RH and LAR for colorectal cancer between 2017 and 2020. All possible preoperative factors were used to explore the risk factors for serious postoperative complication in these very elderly patients with colorectal cancer. Results For RH, the operative mortality rate was 1.1% (98 cases), and the rate of serious postoperative complications was 5.2% (480 cases). Similarly, the mortality rate was 1.1% (27 cases), and the rate of serious complications (Clavien–Dindo Grade ≥3) was 8.7% (206 cases) for LAR. Based on multivariate analysis, independent risk factors for serious postoperative complications were male sex, ADL (partially dependent), hypertension, platelets (<150 000/μL), serum Na (<138 mEq/L), and PT‐INR (>1.1) for RH, and ASA‐PS (Grade ≥3), history of pneumonia, creatinine (>1.2 mg/day), and serum Na (<138 mEq/L) for LAR. Conclusions The present results for RH and LAR suggest that surgical treatment for patients aged ≥85 years old is safe and feasible. Surgeons need to pay special attention more to physical status and past medical history than to tumor factors to prevent serious postoperative complications in these older patients with colorectal cancer.